2008
DOI: 10.1007/s00125-008-1049-1
|View full text |Cite
|
Sign up to set email alerts
|

A modified Mediterranean diet is associated with the greatest reduction in alanine aminotransferase levels in obese type 2 diabetes patients: results of a quasi-randomised controlled trial

Abstract: Aim The aim of the study was to compare the effect of different dietary interventions on alanine aminotransferase (ALT) in obese patients with diabetes. Methods A post hoc analysis of an open label, parallel design, quasi-randomised (allocation by alternation), controlled trial, conducted in Israel. Obese patients with diabetes (n=259), treated in the community, were centrally allocated to one of three diets: (1) the 2003 recommended American Diabetes Association diet (ADA): 50-55% carbohydrate, 30% fat and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 21 publications
3
66
0
3
Order By: Relevance
“…In a 6 month intervention trial, a low-carbohydrate ketogenic diet resulted in a better lipid profile and clearly improved steatosis and inflammation in liver biopsies in comparison to a conventional low-fat diet [66]. Finally, a post hoc analysis of a 1 year weight loss trial conducted in middle-aged obese Israeli patients with type 2 diabetes indicated that a Mediterranean diet reduced alanine aminotransferase levels (a biomarker for NAFLD) to a larger extent than a conventional low-fat diet [67].…”
Section: Carbohydrates and Glucose Homeostasismentioning
confidence: 99%
“…In a 6 month intervention trial, a low-carbohydrate ketogenic diet resulted in a better lipid profile and clearly improved steatosis and inflammation in liver biopsies in comparison to a conventional low-fat diet [66]. Finally, a post hoc analysis of a 1 year weight loss trial conducted in middle-aged obese Israeli patients with type 2 diabetes indicated that a Mediterranean diet reduced alanine aminotransferase levels (a biomarker for NAFLD) to a larger extent than a conventional low-fat diet [67].…”
Section: Carbohydrates and Glucose Homeostasismentioning
confidence: 99%
“…Some food groups (vegetables, legumes, fruit and nuts, cereals, olive oil, wine and fish) are characteristic of the Mediterranean diet and have been frequently used in conjunction with non-characteristic elements (meat, dairy), to give a modified functional definition [2]. The provision of information on food groups would clarify how comparable the study by Fraser et al [1] is to other investigations of this subject.…”
Section: Modified Mediterranean Dietmentioning
confidence: 99%
“…To the Editor: We read with great interest the article by Fraser et al [1], which reported that patients randomised to receive a modified Mediterranean diet (MMD) showed greater reductions in alanine aminotransferase levels at 6 and 12 months compared with those who received the 2003 American Diabetes Association diet or the low glycaemic index diet.…”
Section: Modified Mediterranean Dietmentioning
confidence: 99%
See 2 more Smart Citations